Postconflict behaviour in brown capuchin monkeys (Cebus apella) - Daniel, João Rodrigo (2012)
Postconflict affiliation has been mostly studied in Old World primates, and we still lack comparative research to understand completely the functional value of reconciliation. Cebus species display great variability in social characteristics, thereby providing a great opportunity for comparative studies. We recorded 190 agonistic interactions and subsequent postconflict behaviour in a captive group of brown capuchin monkeys ( Cebus apella) . Only 26.8% of these conflicts were reconciled. Reconciliation was more likely to occur between opponents that supported each other more frequently and that spent more time together. Postconflict anxiety was mostly determined by conflict intensity, and none of the variables thought to measure relationship quality had a significant effect on postconflict stress.